A cognitive model of user interaction as a guideline for designing novel interfaces - Aguilera, Felipe (2006)
Adaptive systems behavior based on user models appear promising, mostly for complex environments such as mixed reality environments (MRE). An MRE comprises a virtual representation of the reality as well as physical objects augmented with virtual features. These objects are coupled with the virtual representation so that they can reflect its changes in real time. The proper design of an MRE and the user models that it implies are crucial for its success, but unfortunately, there are no guidelines for the design of these environments. In this paper we present a methodology for designing user models for MRE as well as for the augmentation of physical everyday objects. The user model describes users’ knowledge in two levels of abstraction: objects manipulation (syntax) and its meaning assigned by a community of practice (semantics).